Tinjauan Radioterapi Kanker Serviks: Mengatasi Tantangan Pelayanan Kesehatan Indonesia - Mirfauddin, Mirfauddin; Nurbeti, Nurbeti; Harun, Herlinda Mahdania (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2023)
Cervical cancer ranks among the leading causes of death worldwide, with Indonesia experiencing a significant impact, ranking second after breast cancer in the country and eighth in Southeast Asia. The disease affects approximately 500,000 Indonesian women annually, resulting in over 50% are death. Various methods have been developed to treat cancer, one of which is by using radiation therapy or radiotherapy. Based on the International Agency for Research on Cancer (IARC), of the 10.9 million people diagnosed with cancer worldwide each year, around 50% require radiotherapy. The use of radiation for cancer therapy has not been widely used and is still limited in Indonesia. The purpose of this paper is to describe the basic concepts of radiotherapy and radiotherapy techniques that are appropriate in treating cervical cancer. The research method used was a literature search in the form of theory and research data related to the basic concept of radiation and its use in cancer therapy/radiotherapy, especially in cervical cancer. The results of a literature search found that the main goal of radiotherapy is to maximize the therapeutic ratio between Tumor Control Probability (TCP) and Normal Tissue Complication Probability (NTCP). Where the radiation dose received by the tumor is as maximal as possible from the dose prescription determined by a clinical doctor, while the dose that affects healthy organs around the tumor is as minimal as possible. There are 2 methods used in radiotherapy treatment, namely internal radiotherapy (Brachytherapy) and external radiotherapy. The use of appropriate methods for the treatment of cervical cancer is expected to help patients in their treatment and reduce the number of deaths from cervical cancer.